(untitled) (Journal of Human Sciences, 2022)
Geographers were interested in crime in studying many dimensions and questions, the most important of which are where crime occurs and in what environment, why some places are more vulnerable to crime than other places, and how the characteristics of the place affect crime and its effects, and thus their focus became on the dimensions of spatial crime and how the place has a role in the occurrence of crime. This urban transformation has led to the emergence of many urban problems such as housing problems, slums and overcrowding, as well as the problem of crime that has grown and spread in most Libyan municipalities, especially those close to international borders, such as the municipality of Sebha, which represents a model and a prominent example for the rapid spread and increase in the volume of crime, especially during the recent The latter is a result of the security chaos and the weakness of the security and police services after the revolution of the seventeenth of February 2011. Although the municipality of Sebha witnessed an increase in the size and spread of the crime phenomenon during the period that followed 2011 due to the weakness of the security and police agencies, there is no study that adopts geographical analysis to understand the spatial reality of this phenomenon in terms of its size, distribution, rates and patterns in the municipality of Sebha. The aim of this study, which follows the change in the phenomenon of crime in the municipality of Sebha in terms of its size, rates, spatial distribution and patterns during the period between 2006 - 2018, the study followed several approaches in order to cover the research objectives of the study; Including the descriptive approach and the use of the quantitative spatial analytical method study.